2008
DOI: 10.2147/tcrm.s1458
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting therapeutic compliance: A review from the patient’s perspective

Abstract: Objective: To explore and evaluate the most common factors causing therapeutic noncompliance. Methods: A qualitative review was undertaken by a literature search of the Medline database from 1970 to 2005 to identify studies evaluating the factors contributing to therapeutic non-compliance. Results: A total of 102 articles was retrieved and used in the review from the 2095 articles identifi ed by the literature review process. From the literature review, it would appear that the defi nition of therapeutic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
281
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 863 publications
(305 citation statements)
references
References 149 publications
(270 reference statements)
9
281
2
13
Order By: Relevance
“…The possible reason might be that older people have more concern about their health than younger patients. 20 The mean duration of hypertension was 5.68±4.37 years. A significantly strong negative correlation (r=-0.133, p=0.012) was found between total treatment compliance score and duration of hypertension ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…The possible reason might be that older people have more concern about their health than younger patients. 20 The mean duration of hypertension was 5.68±4.37 years. A significantly strong negative correlation (r=-0.133, p=0.012) was found between total treatment compliance score and duration of hypertension ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…Though non-adherence to antihypertensive treatment is a significant problem in CHD management few studies on medication adherence have been conducted in developing countries [61]. Moreover, the majority of these studies were conducted in hospital and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The association of sex with adherence has in fact been found to be ambivalent in different studies with some associating it to better adherence, others such as the present one relating it to lower adherence and still no significant association in many of the studies 29 .…”
Section: Fig1: Level Of Adherence Among Study Participants (N=155)mentioning
confidence: 53%
“…According to the review made by Lin et al (2008), sex may not be a god predictor of adherence. Nevertheless, among studies that related sex to adherence is one reported locally from northwestern Ethiopia which reported significant association of the male sex with adherence to antihypertensive medication 15 .…”
Section: Fig1: Level Of Adherence Among Study Participants (N=155)mentioning
confidence: 99%